Cultural representation in three various cover designs of Harry Potter and the Philosopher's Stone - Dhiwangkara, Tresnadian; Ruslianti, Atikah (Lililacs Journal, 2022)
This study aims to look at the cultural representations within the cover of Harry Potter and the Philosopher's Stone from three different countries, namely the United Kingdom, the United States, and Indonesia, and how the cultures of three countries influence the focuses represented on the cover. Using cultural semiotic theory by Yuri Lotman, this research uses a descriptive-analytical method to analyze the visual and verbal texts synchronicly and diachronicly on the basis of temporal context to see the relationship between the culture and the focuses. This study indicates several cultural representations on each cover that can only be seen when these focuses are analyzed with their diachronic aspects. Some of the focuses only appears on one cover and not on the two other covers because there are no correlations between the focus it represents and the culture of that country, so the cover chooses to display other focuses which do have cultural and historical correlations with the country. These cultures are represented and contributed to influence the focuses displayed on the cover. The influence on each focuses could take the form through its pose and portrayal, size comparison, visibility, location, color, and also the style of the illustration itself.